CLIMATE CHANGES AND CHILDREN - Valeriu Popescu (Amaltea Medical Publishing House, 2009)
The increasing temperatures, changing precipitation patterns and more extreme weather events occurring because of climate change have begun to increase morbidity and mortality from climate-sensitive health determinants and outcomes. This review first presents the key issues related to climate change, then presents climate-sensitive health determination and outcomes (extreme weather and heat events; infectious disease; air pollutants and aeroallergens; global assessments to UV radiation) and finishes with a discussion of intergenerational equity and opportunities for reducing current and future vulnerabilities to climate change.